INFLUENTIAL DRIVERS SHAPING THE UPTAKE OF AGILE METHODOLOGIES WITHIN NIGERIA’S MOBILE APPLICATION SECTOR (International Journal of Innovative Technologies in Economy, 2025)
The rapid evolution of Nigeria’s mobile application sector presents unique challenges and opportunities, particularly in the adoption of Agile methodologies. This study explores the influential drivers shaping Agile adoption within this burgeoning industry, addressing key human, organisational, environmental, and technical factors. Through qualitative interviews with Agile professionals, the research identifies critical enablers such as team capabilities, customer involvement, and robust organisational culture. It also highlights constraints posed by limited resources, cultural misalignment, and technical barriers. Findings reveal that while technical tools and delivery strategies play a pivotal role, the interplay of management support, communication, and collaboration emerges as a decisive factor. The study underscores the necessity of tailoring Agile practices to align with Nigeria's socio-economic and technological contexts. By delving into the unique challenges faced by developers, this research provides actionable insights for fostering a sustainable Agile ecosystem in Nigeria. Its findings contribute to the broader discourse on Agile methodologies in emerging markets, offering a foundation for future frameworks that integrate cultural and contextual nuances.